EFEK DARI MENGGUNAKAN TEKNIK MIND MAPPING PADA KEMAMPUAN SISWA KELAS SATU SMA NEGERI 12 PEKANBARU DALAM MENULIS TEKS DESKRIPTIF - Noverly, Rika Noverly Rika; Azhar, Fadly Azhar Fadly; ', Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This pre-experimental design aimed to find out the effect of mind mapping technique in writing descriptive texts. This pre-experimental research was used one-group pretest-posttest design. The sample of this research was the first year students of SMA Negeri 12 Pekanbaru. The partcipants were 39 students. The reasons for conducting this research because of several problems: the students faced some problem in terms of vocabulary and grammar. Furthermore, the students have difficulties to develop their ideas in writing descriptive text. The steps of research procedure are conducting pre-test, treatment, post-test and data analysis. The data were assessed by the three raters and analyzed by using t-test formula. The data analysis showed that the implementation of mind mapping technique as the teaching technique was effective to improve students’ ability in writing descriptive texts. The finding also proved that in the pre-test students’ average score was only 58.72 and it improved to 76.07 in the post-test. In addition, applying mind mapping as a teaching technique in English language teaching and learning could also improve students’ ability to write English in terms of grammar, vocabulary, mechanic, organization, and fluency.Keywords: Mind Mapping Technique, Ability, Writing, Descriptive Text